The relationship of inquiry-based instruction, student's attitudes toward science and teacher's support towards science achievement - Vigneswary, M.Ramachandaramurthy (2011)
Science is studied in various ways. There is no one way set that all students learn science. The purpose of this quantitative study is to seek the relationship between inquiry-based instruction, student's attitudes toward science and teacher's support towards science achievement. It also looks at the gender differences in science achievement. This study was done among 149 students in a national primary school in a rural area in Kedah. Questionnaires were given to the students for feedback. The results indicated that female students perform better in science than male students. In addition the regression results revealed that all three independent variables namely inquiry-based instruction, student's attitudes toward science and teacher's support significantly influence science achievement among year five students. Implications and future direction of studies were also discussed.